Polatuzumab vedotin-R-CHP used for high-risk EBV-negative DLBCL-type post-transplant lymphoproliferative disorder in a long-term kidney transplant recipient: a case report - Jiang, Xiaoyu; Wu, Chunping; Zhang, Yuxun Oswald; Luo, Mingqing; Qiu, Yiwen; Li, Miao; Zhan, Lianshan; Zhong, Daping (Frontiers in Oncology, 2026)
BackgroundPost-transplant lymphoproliferative disorder (PTLD) is a severe life-threatening complication following solid organ transplantation. Among its subtypes, monomorphic PTLD (mPTLD) is the predominant form, most often presenting as diffuse large B-cell lymphoma (DLBCL). Most PTLD is Epstein–Barr virus (EBV) related, and EBV-negative PTLD typically arises later in the post-transplant course.Case descriptionWe report the case of a 57-year-old female who had undergone kidney transplantation 23 years earlier. Routine examination showed elevated serum creatinine and lactate dehydrogenase (LDH) levels, along with tacrolimus concentrations above the therapeutic range. Although asymptomatic, the patient underwent comprehensive evaluation because of the risk of PTLD and graft rejection. Ultrasonography demonstrated multiple masses in the transplanted kidney, and renal biopsy confirmed EBV-negative diffuse large B-cell lymphoma (DLBCL) with a germinal center B-cell (GCB) immunophenotype. An initial clinical response, including partial tumor regression, was observed following a reduction in immunosuppressive therapy and administration of two doses of rituximab. However, the disease progression was confirmed two months later. The patient subsequently underwent six cycles of Pola-R-CHP (polatzumab vedotin, rituximab, cyclophosphamide, adriamycin and dexamethasone; 21-day per cycle). Positron emission tomography/computed tomography (PET/CT) demonstrated regression of the tumor in the transplanted kidney, with a marked reduction in the maximum standardized uptake value (SUVmax). Despite this favorable response, new lesions were detected in the spinal canal of thoracolumbar spine.ConclusionIn this case, Pola–R–CHP achieved a favorable initial response, suggesting a potential role in the management of mPTLD. However, the subsequent central nervous system relapse underscores the need for further studies that incorporating CNS prophylaxis to define its optimal application.